Pengaruh Ketepatan Waktu Visite Dokter terhadap Kepuasan Pasien Rawat Inap Peserta BPJS Kesehatan: Sebuah Tinjauan Pustaka - Situmorang, Cindy (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2025)
Patient satisfaction is a crucial indicator of service quality within Indonesia's National Health Insurance system. For inpatients in the BPJS Kesehatan Class 3 category, a vulnerable population segment, the timeliness of doctor's rounds is a significant factor influencing their experience; thus, this article aims to critically analyze its effect. Employing a narrative literature review methodology, empirical evidence from relevant studies was synthesized and critically analyzed to construct a comprehensive conceptual model. The analysis reveals a positive and statistically significant relationship between the timeliness of doctor's rounds and patient satisfaction. Furthermore, timeliness functions as a "gateway variable," a prerequisite for effective interpersonal communication, and as an "equity signal" for BPJS Class 3 patients, for whom delays risk being interpreted as undignified treatment that can erode trust. In conclusion, improving the timeliness of doctor's rounds is not merely an operational efficiency enhancement but a fundamental strategic intervention. It is essential for improving interpersonal interactions, upholding the principle of fair and dignified treatment, and strengthening patient trust in the JKN program.